PENGARUH CASH HOLDINGS TERHADAP NILAI PERUSAHAAN - Bayu, Albertus; Septiani, Aditya (Diponegoro Journal of Accounting, 2015)
This research investigates the relationship between firm value and cash holdings. Firm value in this research represent the perception of investors about firm profitability which measured by Tobin’s Q and MV/TA. The population in this research includes all manufacture firms listed on the Bursa Efek Indonesia (BEI) over the period 2011- 2013. The samples conducted by purposive sampling method. Total 75 firms is obtained. Data are analyzed by data panel regression technique. Result shows that manufacture firm in Indonesia doesn’t apply optimal cash holdings. This research support the pecking order theory that report there is no optimal cash holdings. Firm’s cash holdings in the end of period would just be the residual of firm operating activities.